The Intersection of Public Health and Human Rights: Legal and Policy Dimensions of Health Justice in Indonesia’s Pandemic Preparedness (Indonesian Health Justice Review, 2025)
The COVID-19 pandemic underscored the crucial intersection of public health, human rights, and government policies. This paper explores the legal and policy dimensions of health justice in Indonesia’s pandemic preparedness, with a focus on the government’s response to the health crisis and its impact on human rights. Using legal analysis and policy reviews, the research examines Indonesia’s public health laws, the country’s participation in international health agreements, and the adequacy of pandemic preparedness plans. The study highlights the challenges in balancing public health measures, such as lockdowns and quarantine protocols, with the protection of human rights, particularly for marginalized groups. It also critiques the allocation of resources during the pandemic and the disproportionate impact on vulnerable populations, including low-income workers and those living in informal settlements. The paper argues that achieving health justice during public health emergencies requires policies that protect both public health and individual rights, ensuring equitable access to healthcare, information, and protective measures. Recommendations include revising pandemic preparedness laws to ensure greater transparency, accountability, and inclusivity in future public health responses, as well as developing comprehensive plans that prioritize the most vulnerable communities.